2019
DOI: 10.1002/pan3.10053
|View full text |Cite
|
Sign up to set email alerts
|

A culturomics approach to quantifying the salience of species on the global internet

Abstract: 1. Conservation will only be successful over the long term if people support conservation goals. While many factors may influence the level of such support, it is clear that people are more willing to conserve species and places that they are familiar with and which provide them with something they value. Until now this dimension has been largely lacking from conservation decision-making and its underlying scientific evidence base. This is understandable given conservation scientists' historic focus on populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 60 publications
2
27
0
Order By: Relevance
“…‘federally protected’ and ‘introduced’) explained the distribution of species with cultural niche space (Schuetz & Johnston, 2019). Many of the effects that we found echoed findings from a range of other studies (Clucas et al., 2008; Cox & Gaston, 2016; Ladle et al., 2019; Lišková & Frynta, 2013; Tisdell et al., 2007) and suggested that a variety of perceptual and cultural biases shape relationships with wildlife in Western cultural contexts. Since lasting conservation impacts may only be realized if we are able to change how other species are viewed, it is important to understand how flexible cultural niches are over time, and why some species may shift more easily through cultural niche space than others as a result of changing perceptual or cultural biases.…”
Section: Introductionsupporting
confidence: 84%
“…‘federally protected’ and ‘introduced’) explained the distribution of species with cultural niche space (Schuetz & Johnston, 2019). Many of the effects that we found echoed findings from a range of other studies (Clucas et al., 2008; Cox & Gaston, 2016; Ladle et al., 2019; Lišková & Frynta, 2013; Tisdell et al., 2007) and suggested that a variety of perceptual and cultural biases shape relationships with wildlife in Western cultural contexts. Since lasting conservation impacts may only be realized if we are able to change how other species are viewed, it is important to understand how flexible cultural niches are over time, and why some species may shift more easily through cultural niche space than others as a result of changing perceptual or cultural biases.…”
Section: Introductionsupporting
confidence: 84%
“…Larger species that are frequently more studied has previously been noted (Ibáñez‐Álamo et al , 2017; Tensen, 2018), and may be related to their higher cultural profile (Frynta et al , 2013; Jepson & Barua, 2015; Macdonald et al ., 2015; Ladle et al . , 2019), and that they are more likely to be hunted, have lower population densities, slower life histories and, consequently, to be at greater risk of extinction (Schipper et al , 2008). Additionally, large species are often more conspicuous and may be easier to study in situ .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have assessed these dynamics over long periods (e.g., Funk & Rusowsky 2014;Proulx et al 2014;Mittermeier et al 2019;Troumbis 2019) or in response to specific events such as conservation interventions, news, movies, and nature documentaries (e.g., Papworth et al 2015;Soriano-Redondo et al 2017;Fernández-Bellon & Kane 2020;Veríssimo et al 2020). Other common applications of culturomics to conservation include identifying culturally salient species and sites (e.g., Roll et al 2016;Correia et al 2018b;Ladle et al 2019) and investigating preferences for naturebased recreation (e.g., Hausmann et al 2018;Monkman et al 2018b;Sbragaglia et al 2019). There are also a number of other topics in which the use of culturomics approaches for conservation is now developing rapidly, including biological invasions (e.g., Fukano & Soga 2019;Jarić et al 2021), illegal wildlife trade (Hinsley et al 2016;Di Minin et al 2018;Di Minin et al 2019), and humanwildlife conflict (Miranda et al 2016).…”
Section: Introductionmentioning
confidence: 99%